Leveraging Entertainment Education for Social Change in the Media - Yadima, Gaius Jeff (EDUMALSYS Journal of Research in Education Management, 2025)
Entertainment-Education (E-E) is a powerful communication strategy that integrates educational messages into entertaining content to influence public attitudes and behaviors. This paper explores the role of edutainment in driving social change, particularly in health and environmental awareness, through various media platforms. By analyzing case studies from television, radio, digital media, and social platforms, the paper examines how E-E has been used to address critical health issues such as disease prevention, maternal health, and hygiene, as well as environmental concerns like climate change and conservation. The study also highlights the theoretical foundations of Entertainment Education theory to explain its effectiveness. Furthermore, challenges such as cultural resistance, funding constraints, and accessibility issues are discussed. Finally, the study recommends incorporation of local cultural narratives, collaboration between stake holders, utilizing digital platforms for wider reach, feedback mechanism and a structured monitoring and evaluation system to optimize E-E strategies for greater impact in media-driven social change.